Density Profile Structure of Eucalyptus regnans Wood - Awoyemi, L.; Wells, P. (Indian Forester, 2003)
The density profile structure of Eucalyptus regnans wood was investigated using X-ray CT scanner and Scion image processor. The earlywood density, latewood density and average wood density are 585 kg/m3 to 699 kg/m3, 730 kg/m3 to 840 kg/m3 and 656 kg/m3 to 781 kg/m3 respectively. The volume of earlywood in this species is higher than the latewood.